The influence of black conscious on post colonial protest poetry: a conscientisation in Mtshali's selected poems - Pheme, Pitsi Petrus (My University, 2020)
This mini dissertation examines the influence of the Black Consciousness Philosophy on Oswald Mbuyiseni Mtshali’s Post-Colonial protest poetry. This is done in the form of analysing selected poems to highlight the influence that the Black Consciousness Philosophy had on the poems that Mtshali wrote about the experiences of black people under a suppressive apartheid system. The aim of this study was to explore how Mtshali’s poetry exposed the extent to which black people had been socio-economically deprived and misled to a negative and false belief of their inferiority and subservience. The title of the mini dissertation, suggests that Black Consciousness poetry claims to have had an influence on the protest poetry of Oswald Mtshali. The poems were analysed to ascertain this. The poems were examined with the express aim of identifying and understanding their themes and the socio-economic context from which they emanate.
Thesis (M.A. (English Studies)) -- University of Limpopo, 2020
Keywords: Black consciousness; Poems; Consciousness philosophy; Apartheid system; Protest poetry; Post- colonial theology; Consciousness